1991
DOI: 10.1016/0014-5793(91)81337-8
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of the K+ transport system in Saccharomyces cerevisiae

Abstract: The stability of the K' transport system in Sacchurornyces cerevisiae has been studied upon inhibition of protein synthesis with cycloheximide. Addition of the antibiotic gave rise lo an inactivation of this transport. This activation followed first-order kinetics and was stimulated by the presence of a fermentable substrate. A half-life of about 4 h could be calculated in the presence of glucose. The results indicate that, similarly to sugar carriers, K' transport system is less stable than the bulk of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, this belief contrasts with the available evidence because it assumes that : (i) the inactivation is speci¢cally produced by glucose while the results show that it is produced by all tested fermentable sugars [20,23]; (ii) the inactivation a¡ects only non-glucose sugar transporters while the results show that all tested plasma membrane proteins, i.e. the uracil [24], inositol [25], and K permeases [26,27], the H -ATPase [28], and even the glucose transporters themselves [27,29,30], are inactivated by a similar mechanism.…”
Section: Introductionmentioning
confidence: 80%
“…However, this belief contrasts with the available evidence because it assumes that : (i) the inactivation is speci¢cally produced by glucose while the results show that it is produced by all tested fermentable sugars [20,23]; (ii) the inactivation a¡ects only non-glucose sugar transporters while the results show that all tested plasma membrane proteins, i.e. the uracil [24], inositol [25], and K permeases [26,27], the H -ATPase [28], and even the glucose transporters themselves [27,29,30], are inactivated by a similar mechanism.…”
Section: Introductionmentioning
confidence: 80%
“…There are numerous examples of yeast plasma membrane proteins that are removed and degraded in response to regulatory cues-i.e., ligand-mediated endocytosis (17,58), nutrient deprivation (15,20,42,47), and control of ion homeostasis (49). Other plasma membrane proteins are subject to high constitutive rates of degradation (5,7,18,39). We report the first example in which a plasma membrane protein is eliminated from the cell surface because of a structural defect.…”
Section: Discussionmentioning
confidence: 97%
“…35°C produced a decrease of about 20% in the ATPase activity of the mutants as compared with the wild-type and the transformed cells ( Table 2) and it has been shown that this low decrease has no significant effect on the K ÷ transport activity [2,15].…”
Section: Resultsmentioning
confidence: 98%
“…Inactivation of the K ÷ and glucose transports were triggered by suspending the cells in a minimal medium as described [9] in the presence of 2% glucose, 10 /zg m1-1 cycloheximide, and the appropriate nutrients. After incubation at 24°C or 35°C for the indicated periods in a rotatory shaker (200 rpm), K ÷ transport activity was measured as described [2]. For this purpose the cells were depleted beforehand of intracellular K ÷ by incubation in the presence of NaN 3 as described earlier [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation